Penggunaan Metode SWOT Untuk Mengembangkan Strategi Pemasaran Warung Kopi Babakan - Nugroho, Muhammad Yusuf; Yunita, Tyna (Prisani Cendekia, 2024)
In the era of increasingly fierce business competition, businesses are required to understand the market better in order to create quality products and superior services for customer satisfaction. This study aims to develop an effective marketing strategy for Warkop Babakan using a SWOT analysis approach. This analysis identifies the strengths, weaknesses, opportunities and threats facing Warkop Babakan, a coffee shop founded by Bang Alim in 2022 in North Bekasi, West Java. The research was conducted using qualitative methods through interviews and direct observation. The results of the SWOT analysis show that the main strengths of Warkop Babakan are complete facilities and a diverse menu, as well as a strategic location. Weaknesses include limited parking space and poorly lit shophouses. Opportunities include increasing visibility through Google Maps and maintaining food and beverage supplies, while threats come from competitors with better facilities and hygiene issues. Marketing strategies designed include product development, competitive pricing, effective promotion, and good customer service. The research conclusion emphasizes the importance of SWOT analysis in devising a comprehensive marketing strategy to improve the competitiveness and sustainable growth of Warkop Babakan's business.